2017
DOI: 10.3748/wjg.v23.i2.191
|View full text |Cite
|
Sign up to set email alerts
|

Evolving strategies for liver fibrosis staging: The non-invasive assessment

Abstract: Transient elastography and the acoustic radiation force impulse techniques may play a pivotal role in the study of liver fibrosis. Some studies have shown that elastography can detect both the progression and regression of fibrosis. Similarly, research results have been analysed and direct and indirect serum markers of hepatic fibrosis have shown high diagnostic accuracy for advanced fibrosis/cirrhosis. The prognosis of different stages of cirrhosis is well established and various staging systems have been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Although CT-PMWA is a kind of minimal invasive therapies, preoperative hepatic function reserve was significantly associated with the long-term prognosis of patients. Our findings were consistent with previous studies [18][19][20][21][22][23][24][25][26]. Therefore, the better patients' hepatic function reserve was assessed, the better patients' prognosis could be evaluated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although CT-PMWA is a kind of minimal invasive therapies, preoperative hepatic function reserve was significantly associated with the long-term prognosis of patients. Our findings were consistent with previous studies [18][19][20][21][22][23][24][25][26]. Therefore, the better patients' hepatic function reserve was assessed, the better patients' prognosis could be evaluated.…”
Section: Discussionsupporting
confidence: 92%
“…The Child-Pugh classification system is widespread used to assess hepatic function reserve [18][19][20], but the subjective factors such as severity of ascites and degree of hepatic encephalopathy usually affect the assessment ability. Comparing to the Child-Pugh class, the albumin-bilirubin (ALBI) grade is associated with two important characteristics, which are simple and objective.…”
Section: Introductionmentioning
confidence: 99%
“…There is solid evidence supporting the fact that liver fibrosis is potentially reversible as long as a certain "point of no return" is not exceeded. Therefore, it is of fundamental importance to diagnose and assess the severity of liver fibrosis in order to permit risk stratification and provide appropriate management for preventing ongoing liver injury and cirrhosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…10 Also, there is an increasing number of ongoing studies for this purpose. 22 Measuring serum ACE levels is one of them, showing promising results in early studies, although some paradoxical outcomes have also been reported recently. [16][17][18]23 The issue of non--invasive methods has increasingly attracted many researchers, and frequently new studies on the topic are added to the literature.…”
Section: Resultsmentioning
confidence: 99%